PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Herlin Aria Winata; Budi Koestoro; Dwi Yulianti (Indonesia Journal of Educational Technology, 2017)
This research aimed to analyze (1) learning process, (2) increasing of study achievement. Method of research used classroom action research by three cycles. The first cycle use guided inquiry, experiment equipment and students worksheet. Second cycle of guided inquiry by power point learning media. Third cycle used guided inquiry by lesson book and article lesson. The conclusion of research are : (1) guided inquiry are able to increas teachers activities in pre-activityduring learning process, (2) guided inquiry leraning can increase students study achievement. It can be seen from class VIII.a students cognitif score at first cycle was 47,19 (failed) and class VIII.b was 46,88 (failed), second cycle at class VIII.a was 65 (passed) and classs VIII.b 60 (failed), and third cycle at class VIII.a was 75 (passed) and at class VIII.b was 72 (passed).Penelitian ini bertujuan untuk menganalisis (1) proses pembelajaran; (2) peningkatan hasil belajar. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas dengan tiga siklus. Siklus pertama dengan inkuiri terbimbing dan alat praktikum serta LKS. Siklus kedua inkuiri terbimbing dengan media pembelajaran powerpoint. Siklus ketiga inkuiri terbimbing dengan buku cetak dan artikel pembelajaran. Kesimpulan dari penelitian ini adalah: (1) inkuiri terbimbing mampu meningkatkan aktivitas guru dalam kegiatan pra pembelajaran, pelaksanaan pembelajaran, dan penutup pembelajaran; (2) pembelajaran inkuiri terbimbing dapat meningkatkan hasil belajar peserta didik dengan nilai kognitif peserta didik pada siklus I di kelas VIII.A 47,19 (tidak tuntas) dan di kelas VIII.B 46,88 (tidak tuntas), siklus II di kelas VIII.A 65 (tuntas) dan dikelas VIII.B 60 (tidak tuntas), siklus di kelas VIII. A 75 (tuntas) dan di kelas VIII.B 72 (tuntas).Kata kunci: hasil belajar, inkuiri terbimbing, kendali